Carpal tunnel syndrome - Part II (treatment), - Michel Chammas; Jorge Boretto; Lauren Marquardt Burmann; Renato Matta Ramos; Francisco Santos Neto; Jefferson Braga Silva (Revista Brasileira de Ortopedia, 2014)
The treatments for non-deficit forms of carpal tunnel syndrome (CTS) are corticoid infiltration and/or a nighttime immobilization brace. Surgical treatment, which includes sectioning the retinaculum of the flexors (retinaculotomy), is indicated in cases of resistance to conservative treatment in deficit forms or, more frequently, in acute forms. In minimally invasive techniques (endoscopy and mini-open), and even though the learning curve is longer, it seems that functional recovery occurs earlier than in the classical surgery, but with identical long-term results. The choice depends on the surgeon, patient, severity, etiology and availability of material. The results are satisfactory in close to 90% of the cases. Recovery of strength requires four to six months after regression of the pain of pillar pain type. This surgery has the reputation of being benign and has a complication rate of 0.2–0.5%.